THE EFFECT OF IMPLEMENTATION OF IFRS OF QUALITY MEASUREMENT OF FINANCIAL REPORTING BASED ON QUALITIATIVE CHARACTERS IN SOME ASEAN COUNTRIES - Santoso, Kristian; Suciati, NR. Handiani (Jurnal Ekonomi dan Bisnis Terapan, 2018)
This study aim to analyse the influence of IFRS implementation on the quality of financial reporting measured by qualitative characteristic developed by NiCE; Relevance, Faithful Representation, Understandability, Comparability, and Timeliness. 53 Manufacturing companies that listed at Indonesian Stock Exchange (IDX), Kuala Lumpur Stock Exchange (KLSE), and Singapore Stock Exchange (SGX) were used as the sample based on purposive sampling method. The data analyzed using paired sample t test or Wilcoxon test for data which is not fulfil normal distribution. Based on test we found that there is significant differences in quality of financial reporting between pre and post IFRS implementation in those countries